Coexisting pathology of ectopic pregnancy and dermoid cyst: An uncommon occurrence (Indian Journal of Case Reports, 2018)
Mature cystic teratomas (dermoid cysts) are common benign ovarian neoplasms. About 10% of dermoid cysts are detected during pregnancy. Multiple gynecologic pathologies occurring together are uncommon, and both an ectopic pregnancy and dermoid cyst are seen concurrently being unknown and poorly documented. Here, we report a case of ectopic pregnancy and dermoid cyst occurring simultaneously in a 30-year-old woman.